(untitled) (Fiep Bulletin - online, 2013)
The objective of this study was to define the lifestyle and well-being of workers of the operational sector of Companhia Rio Grandense de Saneamento (CORSAN). Seventeen workers participated in the research, among which sixteen were male and one female, with age range from 27 to 57 years-old, all from Santa Cruz do Sul/RS. The methodological approach was characterized as study of the descriptive-exploratory type, being an integrant part of the Occupational Health and Lifestyle Project, approved by the Ethics Committee at Universidade de Santa Cruz do Sul UNISC. In the data collection, blocks of the referred project were used, referring to the Identification, social and economical indicators; Daily organization; Health indicators; General aspects of lifestyle and well-being, aiming at characterizing the lifestyle profile and worker’s health. The data were analyzed within blocks, through the descriptive statistics, pointing out, in relation to the food, that 47.2% of the subjects include, sometimes, five portions of fruit and vegetables, although 41.2% of the interviewed do not have four to five varied meals daily. In relation to the physical activity, 52.9% do strength exercises and stretching twice a week and approximately the same number does aerobic exercises. As to the social relationships, they cultivate friendships and are satisfied with their relationships. In the preventive aspects, they can discuss without changing their mood and balance the time dedicated to work and leisure. We highlight that the investigated subjects show healthy habits in relation to the preventive cares, in relation to the physical activity and social relationships, neglecting, however, in the nutritional aspects. The profile of the analyzed workers in this study may not reflect the reality of the labor world, which recommends the interventions of promotion of the occupational health in other scenarios.